BIOLOGY OF YELLOW SELAR FISH (Caranx leptolepis) AND ICE PRESERVED PROTEIN, LIPID AND CARBOHYDRATE CONTENT - Jeffry Raturandang; Femmy Rogahang; Fandi Tuju (Indonesian Biodiversity Journal, 2021)
Yellow Selar fish (Caranx leptolepis) as pelagic fish are mostly caught by fishermen in North Sulawesi. However, from observations and preliminary research, fishermen often do not pay attention to fish sustainability because even small fish are caught. This is motivated by the lack of knowledge of fishermen and the lack of research on yellow selar fish in Sulawesi. Research has been carried out with the aim of obtaining the Biological Characteristics of Yellow Selar fish caught by fishermen in North Sulawesi. Obtaining the biochemical characteristics of selar kuning fish (macronutrient content). The results that have been achieved: The average total length of Caranx leptolepis without distinguishing males and females is 180 mm and weighs 90 gr. Fish gonad maturity index is between 1.02 to 1.90. From the stomach contents that we observed, the types of food eaten included small fish and shrimp. A total of 96% of small fish and 4% of shrimp were found in the stomach contents of the slugs that were analyzed. Protein and Fat content of Selar fish decreased with the length of storage time using ice. However, the carbohydrate content remained relatively unchanged. The best storage time for tude on ice is 48 hours. More than 48 hours there is a very significant decrease in protein and fat content.